Entre la contención y el desarollo competencial: una aproximación al objeto-sujeto en el Trabajo Social - Gurbindo Marín, Miguel Ángel (Cuadernos de Trabajo Social, 2008)
In the age of postmodernism, Social Work is developing within a complex ever-changing context. This fact makes many social activities take place in a continuum constrained by opposite theoretical frameworks or paradigms. Therefore, Social Workers need to make a critical analysis of the models, methods and methodolgy of their interventions at hand, in order to behave not only out of self-control and containment, but also out of recognition, respect and the development of competence. All this is necessary in order to clarify the difficulties of the interventions involved whithin a perspective where the individual / customer is an active subject of his/her own changing process.
Keywords: Competences; Containment; Complexity; Individual; Subject; Object